Ultrasonographic evaluation of lung and heart in predicting successful weaning in mechanically ventilated neurosurgical patients - Sachin, Sasidharan (J Clin Monit Comput, 2020)
In critically ill neurosurgical patients, delayed and premature extubation increases the risk of morbidity and mortality. Assessment of critically ill patients before and during spontaneous breathing trial (SBT) is crucial in predicting weaning failure. We explored the trend of changes with integrated lung and cardiac ultrasonography in predicting success of weaning in neurosurgical patients. Lung ultrasound and cardiac ultrasound was performed before and after 30 min and 120 min of SBT. Lung ultrasound score (LUS, range 0–36) was calculated using a predefined method of assessment of six chest regions on either side. The left ventricular function was evaluated by measuring fractional area change. The maximum velocities of mitral inflow E and A waves (E/A), deceleration time of E wave (DTE) and tissue doppler based E′ wave at lateral annulus to calculate E/E′, were measured to assess left ventricular filling pressure. Twenty seven patients underwent SBT, among these 22 had success and five had failure of SBT. The SBT failure group had higher baseline LUS and progressively higher LUS during SBT compared to the success group, suggesting significant lung de-recruitment. There was significant increase in the LV filling pressure (increase E/A and E/E′, decrease in DTE) after 30 and 120 min of SBT in failure group compared to the success group. Point of care lung and cardiac ultrasonography may be useful in detecting cardiopulmonary changes induced by SBT. Higher lung aeration loss and LV filling pressure were observed with SBT failure group.